The influence of learning styles and thinking styles on self–regulated learning among high school students - Nurkusuma, Alfisahri; Hasanuddin, Hasanuddin; Dewi, Salamiah Sari (Universitas Ahmad Dahlan, 2025)
In response to evolving educational demands, students are increasingly expected to take ownership of their learning, particularly in environments characterized by high academic pressure and teacher-centered instruction. Self-regulated learning (SRL) plays a crucial role in enabling students to plan, monitor, and evaluate their cognitive strategies, motivation, and behavior to achieve academic success. This study investigates how internal factors, specifically learning styles and thinking styles, influence SRL among high school students. A quantitative approach was employed, using multiple linear regression in SPSS version 20. The research involved 315 students from Perguruan Panca Budi in Medan, selected through proportional stratified sampling. The results indicated that the regression model was statistically significant (F=4079.49, p<0.001), with learning styles emerging as a strong predictor of SRL (β=0.848, p<0.0001). In contrast, thinking styles did not demonstrate a significant effect (β=0.135, p=0.103). The VIF values for both predictors were 2.723, well below accepted thresholds, confirming the absence of multicollinearity and indicating that the multiple regression assumptions were satisfied. Emphasizing students' preferred learning approaches may enhance their autonomy, motivation, and engagement. This study highlights the importance of adaptive teaching strategies that account for individual learning differences, offering practical insights for educators seeking to strengthen SRL in the classroom.